Kontrol Kecepatan Putaran Permanent Magnet Synchronous Machine (PMSM) Menggunakan PID, FLC Dan ANFIS - Machrus Ali; Muhlasin Muhlasin (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
Permanent Magnet Syschronous Machine (PMSM) has low torque in a number of specific applications, so a good control model is needed. PMSM uses the principle of faraday experiments by turning a magnet in a coil by utilizing another energy source ... When a magnet moves in a coil or vice versa. Turning the engine will change the magnetic force flux in the coil and penetrate perpendicular to the coil so that there is a potential difference between the ends of the coil. That is due to changes in magnetic flux. To get the best control method, a comparison of several speed control models is needed. In this study comparing PMSM speed control without controller, using PID controller, using FLC controller, and using ANFIS controller. From the simulation results show that the best model on ANFIS controller, which is closest to the Speed reff (300 rpm) is ANFIS obtained the round profile with the smallest undershot of 300,015 rpm at t = 0.0055 seconds and steady state at 300.02 rpm at 0.004 seconds, obtained output current profile best on FLC = 3.39 A, while at ANFIS = 3.38 A, the best torque profile (the smallest overshot) is obtained on the ANFIS controller of 0.28 pu, the best voltage profile (most continuous) on the ANFIS controller is 300.03. The results of this study will be continued with the use of other artificial intelligence.